Completion of Fandorin’s quasibiography: B. Akunin «Do not say goodbye» (Literatures of the World: Poetics, Mentality and Spirituality, 2018)
The article analyzes the conclusion in the novel «Do not say goodbye» to the quasibiography of Erast Petrovich Fandorin, the hero of many novels, tales, stories by Boris Akunin. For achieving this, the author considers a novel in which the actors themselves are Fandorin, his faithful companion Masahiro Sibata and his wife Elizabeth and many other heroes whose prototypes are recognizable. The events take place during the period of the Civil War in Russia. Some fragments of the novel reproduce events in Ukraine, in particular in Kharkiv. B. Akunin in his novel «Do not say goodbye», as in a number of his other works, is trying to represent the quasibiography of Fandorin like a biography of a real person who lived and worked in the context of true historical events of his time.
Keywords: quasi biography; biography; extrapolation; mystification; detective